An Unusual Cause of Camptocormia. (13th February 2019) - Mehta, Sahil; Kumar, Rajender; Lal, Vivek
Background: Camptocormia is defined as forward flexion of the spine that manifests during walking and standing and disappears in recumbent position. The various etiologies include idiopathic Parkinson's disease, multiple system atrophy, myopathies, degenerative joint disease, and drugs. Case Report: A 67-year-old diabetic female presented with bradykinesia and camptocormia that started 1 year prior to presentation. Evaluation revealed levosulpiride, a dopamine receptor blocker commonly used for dyspepsia, to be the culprit. Discussion: It is well known that dopamine receptor blockers cause parkinsonism and tardive syndromes. We report a rare and unusual presentation of camptocormia attributed to this commonly used gastrointestinal drug in the Asian population.